Population Pharmacokinetics and Pharmacodynamics of Ontamalimab (SHP647), a Fully Human Monoclonal Antibody Against Mucosal Addressin Cell Adhesion Molecule‐1 (MAdCAM‐1), in Patients With Ulcerative Colitis or Crohn's Disease. (2nd March 2020) - Wang, Yi; Marier, Jean‐Francois; Lavigne, Jean; Kassir, Nastya; Martin, Patrick
Abstract: Ontamalimab (SHP647) is a fully human, immunoglobulin G2, antihuman mucosal addressin cell adhesion molecule‐1 (MAdCAM‐1) monoclonal antibody being developed for the treatment of ulcerative colitis (UC) and Crohn's disease (CD). A population pharmacokinetic/pharmacodynamic (PK/PD) analysis was conducted using clinical phase 2 study data to evaluate the PK and PD of ontamalimab following subcutaneous administrations of 7.5, 22.5, 75, and 225 mg every 4 weeks in patients with moderate to severe UC or CD. A total of 440 patients with UC (n = 249; 56.6%) or CD (n = 191; 43.4%) were included in the analysis. A 2‐compartment model with parallel linear and nonlinear elimination adequately characterized concentration‐time profiles of ontamalimab. The apparent clearance and volume of distribution were 0.0127 L/h (0.305 L/day) and 6.53 L, respectively. Apparent clearance and volume of distribution were mainly dependent on baseline albumin and body weight, respectively. No differences in the PK properties of ontamalimab were observed between patients with UC or CD. The presence of antidrug antibodies did not impact the PK of ontamalimab. Nonlinear elimination occurred at very low concentrations and was unlikely to contribute to the elimination half‐life under steady‐state conditions. A linear PK/PD model described the relationship between ontamalimab and free MAdCAM‐1. Minimum concentrations of ontamalimab at steady state following 75 mg every 4 weeks were associated with >95% suppression of circulating free MAdCAM‐1. The PK/PD properties characterized support phase 3 testing in UC and CD.